NILAI KEPEMIMPINAN BAGI ANAK USIA DINI DALAM BUKU UMAR BIN KHATTAB JAGOANKU KARYA ULFAH H.T - Marwany Marwany; Heru Kurniawan; Imroatun Imroatun; Yuyun Ayu Lestari (UIN Sultan Maulana Hasanuddin Banten, 2023)
This research examines the storybook Umar Bin Khattab Jagoanku by Ulfah H.T Dan Reini related to the value of leadership for early childhood in the story. The example of the leader in the story is a friend of the Prophet and the second Caliph, Umar Bin Khattab. The purpose of this study was to analyze the value of leadership in early childhood in the storybook Umar Bin Khattab Jagoanku Karya Ulfah H.T Dan Reini. This type of research is descriptive qualitative with a textual analysis approach or library research in the form of a literature review. Source data from Umar Bin Khattab Jagoanku storybook. Data collection is carried out by reading, understanding, recording, analyzing by collecting, conceptualizing, filtering and sorting out matching data. Data analysis is performed by reducing data, classifying data, and verifying data information. The results of the study found and identified that the value of leadership in the storybook Umar Bin Khattab Jagoanku by Ulfah H.T Dan Reini is shown through an attitude of protection, a brave attitude and an attitude of doing good